Magnetically Separable Cu-Carboxylate MOF Catalyst for the Henry Reaction - Arai, Takayoshi; Kawasaki, Nao; Kanoh, Hirofumi (Synlett, 2012)
An air-stable Cu-carboxylate MOF complex can catalyze the cross-coupling reaction of phenylacetylene with 2-oxazolidone and Henry reaction. The Cu-carboxylate MOF encapsulated magnetic beads (MOF-MB II) was also prepared. The MOF-MB II was successfully reused in the Henry reaction by a simple magnetic separation.
Keywords: catalyst; metal-organic framework; magnetic separation; reuse